Distinctive neuronal firing patterns in subterritories of the subthalamic nucleus. Issue 11 (November 2016) - Pozzi, Nicolò G.; Arnulfo, Gabriele; Canessa, Andrea; Steigerwald, Frank; Nickl, Robert; Homola, György A.; Fato, Marco M.; Matthies, Cordula; Pacchetti, Claudio; Volkmann, Jens; Isaias, Ioannis U.
Highlights: We studied the neuronal activity of STN subterritories as anatomically defined on fused CT/MRI images. We showed that STN subterritories exhibit a distinctive burst firing rate. The different bursting activity might reflect the functional organisation of the STN. Abstract: Objective: Deep brain stimulation of the subthalamic nucleus (STN–DBS) is an established treatment for Parkinson's disease (PD). Anatomical connectivity analyses and task-related physiological studies have divided the STN into different functional domains: sensorimotor, limbic, and associative – located in its dorsolateral (dSTN), anteroventral (vSTN) and medial territories, respectively. Targeting sensorimotor STN is essential for stimulation efficacy and is supported by intraoperative micro-electrode recordings. A different neuronal signature in microelectrode recordings across STN subterritories was explored in this study. Methods: Stable recordings from 30 PD patients were assigned to dSTN or vSTN by means of an anatomical method (based on fused computed tomography/magnetic resonance images) and through a priori tri-segmented partition of the recording itself. We computed the inter-spike interval (ISI) and ISI-characteristics, mean firing rate (MFR), discharge patterns and mean burst rate (MBR) of each detected single unit activity. Results: We showed a different MBR between dSTN and vSTN (1.51 ± 0.18 vs. 1.76 ± 0.22 events/minute, Wilcoxon rank sum test, p < 0.05) and a trend in the difference between their MFR (12.78 vs. 15.05 Hz, Wilcoxon rank sum test, p = 0.053) only with the anatomically based method. Conclusion: Burst firing differs across STN subterritories. Significance: Different functions of subthalamic domains might be reflected by distinctive burst signalling of its subterritories.